Você está na página 1de 8

SolvingLogarithmicEquations

DecidingHowtoSolveLogarithmicEquation Whenaskedtosolvealogarithmicequationsuchas log 2(5x + 7) =5 orlog 3 (7x + 3) = log 3(5x +9), thefirst thingweneedtodecideishowtosolvetheproblem.Somelogarithmicproblemsaresolvedbysimply droppingthelogarithmswhileothersaresolvedbyrewritingthelogarithmicprobleminexponentialform. Howdowedecidewhatisthecorrectwaytosolvealogarithmicproblem? Thekeyistolookattheproblem anddecideiftheproblemcontainsonlylogarithmsoriftheproblem hastermswithoutlogarithms. Ifweconsidertheproblemlog 2(5x + 7) =5, thisproblemcontainsaterm,5,thatdoesnothavealogarithm. So, thecorrectwaytosolvethesetypesoflogarithmicproblemsistorewritethelogarithmicproblemin exponentialform.Ifweconsidertheexamplelog 3 (7x + 3) = log 3(5x + 9), thisproblemcontainsonly logarithms.So, thecorrectwaytosolvethesetypesoflogarithmicproblemsistosimplydropthe logarithms. Propertiesof LogarithmsRevisited Whensolvinglogarithmicequation,wemayneedtousethepropertiesoflogarithmstosimplifythe problemfirst.Thepropertiesoflogarithmsarelistedbelowasareminder. PropertiesforCondensingLogarithms Property1: 0 =log a1 ZeroExponentRule Property2: 1 =log a a Property3: log a x + log a y =log a(xy) ProductRule x Property4: log a x - log a y = log a QuotientRule y Property5: y log a x =log a x y PowerRule SolvingLogarithmicEquationsContainingOnlyLogarithms Afterobservingthatthelogarithmicequationcontainsonlylogarithms,whatisthenextstep? OneToOnePropertyofLogarithms Iflog b M =log b N, thenM=N. Thisstatementsaysthatif anequationcontainsonly twologarithms,onoppositesidesoftheequalsign, with thesamebasethentheproblemcanbesolvedby simply droppingthelogarithms.

Letsfinishsolvingtheproblemlog 3 (7x + 3) = log3(5x +9). log3 (7x + 3) = log3(5x +9). Sincetheproblemhasonlytwologarithmsonopposite sidesoftheequalsign,theproblemcanbesolvedby droppingthelogarithms. Dropthelogarithms. Finishsolvingbysubtracting5xfromeachside,subtracting 3fromeachside,andfinallydividingeachsideby2. Checktheanswerthisisanacceptableanswerbecausewe getapositivenumberwhenitispluggedbackin.

7x + 3 = 5x +9 x =3

x =3

Therefore,thesolutiontotheproblemlog 3 (7x + 3) = log3(5x +9) isx=3. Hereisanotherexample,solvelog 7 (x - 2) + log 7 (x + 3) =log 714. log 7 ((x - 2)(x + 3)) =log 714
(x - 2)(x + 3) =14

Thisproblem canbesimplifiedbyusingProperty3which changestheaddition of logarithmstomultiplication. Dropthelogarithms. SimplifytheproblembydistributingorFOILingand combiningliketerms. Solvetheproblembysubtracting14fromeachtogetit equaltozero,andthenfactoringor usingthequadratic formulatofindthevaluesofx.

x 2 - x - 6 =14
x 2 - x - 20 = 0 (x + 4)(x - 5) = 0 x = -4 or x =5

x=5

Checktheanswers,onlyoneanswerisacceptablebecause theotheranswerproducesanegativenumberwhenitis pluggedbackin.

Therefore,thesolutiontotheproblemlog 7 (x - 2) + log 7 (x + 3) =log 714 isx=5. Nowthatwehavelookedatacoupleofexamplesofsolvinglogarithmicequationscontainingonly logarithms,letslistthestepsforsolvinglogarithmicequationscontainingonlylogarithms.

StepsforSolvingLogarithmicEquationsContainingOnlyLogarithms Step1: Determineiftheproblemcontainsonlylogarithms.Ifso,gotoStep2.Ifnot,stopanduse theStepsforSolvingLogarithmicEquationsContainingTermswithoutLogarithms. Step2: Usethepropertiesoflogarithmstosimplifytheproblemifneeded.Iftheproblemhas morethanonelogarithmoneithersideoftheequalsignthentheproblemcanbe simplified. Step3: Rewritetheproblemwithoutthelogarithms. Step4: Simplifytheproblem. Step5: Solveforx. Step6: Checkyouranswer(s).Rememberwecannottakethelogarithmofanegativenumber,so weneedtomakesurethatwhenweplugouranswer(s)backintotheoriginalequationwe getapositivenumber.Otherwise,wemustdropthatanswer(s).

SolvingLogarithmicEquationsContainingTermswithoutLogarithms Afterobservingthatthelogarithmicequationcontainstermswithoutlogarithms,whatisthenextstep?The nextstepistosimplifytheproblemusingthepropertiesoflogarithmsandthentorewritethelogarithmic probleminexponentialform.Afterrewritingtheprobleminexponentialformwewillbeabletosolvethe resultingproblem. Letsfinishsolvingtheproblem log 2(5x + 7) =5 fromearlier. log 2(5x + 7) =5 5x + 7 =25 5x + 7 =32 x =5 Thisproblemdoesnotneedtobesimplifiedbecausethere isonlyonelogarithmintheproblem. Rewritetheprobleminexponentialformbymovingthe baseofthelogarithmtotheotherside. Simplifytheproblem byraising2tothefifthpower. Solveforxbysubtracting7fromeachsideandthen dividingeachsideby 5. Checktheanswerthisisanacceptableanswerbecausewe getapositivenumberwhenitispluggedbackin.

x=5

Therefore,thesolutiontotheproblemlog 2(5x + 7) =5 isx=5.

Hereisanotherexample,solve ln(4x - 1) =3. ln(4x - 1) =3 Thisproblemdoesnotneedtobesimplifiedbecausethere isonlyonelogarithmintheproblem. Rewritetheprobleminexponentialformbymovingthe baseofthelogarithm totheotherside.Fornatural logarithmsthebaseise. Simplifytheproblem by cubinge.Roundtheansweras appropriate,theseanswerswilluse6decimalplaces. Solveforxby adding1toeachsideandthendividingeach sideby 4. Checktheanswerthisisanacceptableanswerbecausewe getapositivenumberwhenitispluggedbackin.

4x - 1 =e3

4x - 1 20.085537

x 5.271384

x 5.271384

Therefore,thesolutiontotheproblem ln(4x - 1) =3 isx 5.271384. Nowthatwehavelookedatacoupleofexamplesofsolvinglogarithmicequationscontainingtermswithout logarithms,letslistthestepsforsolvinglogarithmicequationscontainingtermswithoutlogarithms. StepsforSolvingLogarithmicEquationsContainingTermswithoutLogarithms Step1: Determineiftheproblemcontainsonlylogarithms.Ifso,stop anduseStepsforSolving LogarithmicEquationsContainingOnlyLogarithms.Ifnot,gotoStep2. Step2: Usethepropertiesoflogarithmstosimplifytheproblemif needed.Iftheproblemhas morethanonelogarithmoneithersideoftheequalsignthentheproblemcanbe simplified. Step3: Rewritetheprobleminexponentialform. Step4: Simplifytheproblem. Step5: Solveforx. Step6: Checkyouranswer(s).Rememberwecannottakethelogarithmofanegativenumber,so weneedtomakesurethatwhenweplugouranswer(s)backintotheoriginalequationwe getapositivenumber.Otherwise,wemustdropthatanswer(s).

ExamplesNowletsusethestepsshownabovetoworkthroughsomeexamples.Theseexampleswillbea mixtureoflogarithmicequationscontainingonlylogarithmsandlogarithmicequationscontainingterms withoutlogarithms. Example1:Solve log 3(9x + 2) =4 log 3(9x + 2) = 4 log 3(9x + 2) =4 9x + 2 =34 9x + 2 =81
x = 79 9 79 9

Thisproblemcontainstermswithoutlogarithms. Thisproblemdoesnotneedtobesimplifiedbecausethere isonlyonelogarithmintheproblem. Rewritetheprobleminexponentialformbymovingthe baseofthelogarithmtotheotherside. Simplifytheproblem by raising3tothefourthpower. Solveforxbysubtracting2fromeachsideandthen dividingeachsideby9. Checktheanswer thisisanacceptableanswerbecausewe getapositivenumberwhenitispluggedbackin.
79 . 9

x =

Therefore,thesolutiontotheproblemlog 3(9x + 2) =4 isx = Example2:Solve log 4 x + log 4(x - 12) =3 log 4 x + log 4(x - 12) =3 log 4(x(x - 12)) =3
x(x - 12) =43

Thisproblemcontainstermswithoutlogarithms. Thisproblem canbesimplifiedbyusingProperty3which changestheaddition of logarithmstomultiplication. Rewritetheprobleminexponentialformbymovingthe baseofthelogarithmtotheotherside. Simplifytheproblem bydistributingandcubingthe4. Solvetheproblemby subtracting64fromeachtogetit equaltozero, andthenfactoringor usingthequadratic formulatofindthevaluesofx.

x 2 - 12x =64
x 2 - 12x - 64 = 0 (x + 4)(x - 16) = 0 x = -4 or x =16 x =16

Checktheanswers,onlyoneanswerisacceptablebecause theotheranswerproducesanegativenumberwhenitis pluggedbackin.

Therefore,thesolutiontotheproblemlog 4 x + log 4(x - 12) =3 isx=16.

Example3:Solve log 4 (2x + 1) = log 4 (x + 2) -log 4 3 log 4 (2x + 1) = log 4 (x + 2) -log 4 3


x + 2 log 4 (2x + 1) = log 4 3 2x + 1= x + 2 3

Thisproblemcontainsonlylogarithms. Thisproblem canbesimplifiedbyusingProperty4which changesthesubtraction of logarithmstodivision. Dropthelogarithms.

3(2x + 1) = x +2

Simplifytheproblembycrossmultiplyingtogetridofthe fractions. Solvetheproblemby distributingthe3,subtractingxfrom eachside,subtracting3from eachside,andfinallydividing by5.

6x + 3 = x + 2 x= 1 5

NoSolution

Checktheanswers,thisproblemhasNoSolution becausetheonlyanswerproducesanegativenumberand wecanttakethelogarithmofanegativenumber.

Therefore,theproblemlog 4 (2x + 1) = log 4 (x + 2) -log 4 3 hasnosolution. Example4:Solve log(5x - 11) =2


log(5x - 11) =2 log(5x - 11) =2

Thisproblemcontainstermswithoutlogarithms. Thisproblemdoesnotneedtobesimplifiedbecausethere isonlyonelogarithmintheproblem. Rewritetheprobleminexponentialformbymovingthe baseofthelogarithmtotheotherside.Forcommon logarithmsthebaseis10. Simplifytheproblem bysquaringthe10. Solveforxby adding2toeachsideandthendividingeach sideby 5. Checktheanswerthisisanacceptableanswerbecausewe getapositivenumberwhenitispluggedbackin.

5x - 2 =102

5x - 2 =100 102 x = 5 102 x = 5

102 Therefore,thesolutiontotheproblem log(5x - 11) =2 isx = . 5

Example5:Solve log 2 (x + 1) - log 2(x - 4) =3 log 2 (x + 1) - log 2(x - 4) =3


x + 1 log 2 = 3 x - 4 x + 1 3 = 2 x -4 x + 1 = 8 x -4

Thisproblemcontainstermswithoutlogarithms. Thisproblem canbesimplifiedbyusingProperty4which changesthesubtraction of logarithmstodivision. Rewritetheprobleminexponentialformbymovingthe baseofthelogarithmtotheotherside. Simplifytheproblem bycubingthe2.

x + 1 = 8(x - 4) x + 1 = 8x - 32 33 7 33 x = 7 x=

Solveforxby crossmultiplying,distributing,subtracting 8xfromeachside,subtracting1fromeachside,andfinally dividingeachsideby 7.

Checktheanswerthisisanacceptableanswerbecausewe getapositivenumberwhenitispluggedbackin.
33 . 7

Therefore,thesolutiontotheproblemlog 2 (x + 1) - log 2(x - 4) =3 isx = Example6:Solvelog 6 (x + 4) + log 6 (x - 2) =log 6(4x) log 6 (x + 4) + log 6 (x - 2) =log 6(4x) log 6 ((x + 4)(x - 2)) =log 6(4x)
(x + 4)(x - 2) =4x

Thisproblemcontainsonlylogarithms. Thisproblem canbesimplifiedbyusingProperty3which changestheadditionoflogarithmstomultiplication. Dropthelogarithms. Simplifytheproblem bydistributingorFOILingand combiningliketerms. Solvetheproblembysubtracting4xfromeachtogetit equaltozero,andthenfactoringor usingthequadratic formulatofindthevaluesofx.

x 2 + 2x - 8 =4x
x 2 - 2x - 8 = 0 (x + 2)(x - 4) = 0 x = -2 or x =4
x=4

Checktheanswers,onlyoneanswerisacceptablebecause theotheranswerproducesanegativenumberwhenitis pluggedbackin.

Therefore,thesolutiontotheproblemlog 6 (x + 4) + log 6 (x - 2) =log 6(4x) isx=4.

AdditionExamples Ifyouwouldliketoseemoreexamplesofsolvinglogarithmicequations,justclickonthelinkbelow. Additional Examples PracticeProblems Nowitisyourturntotryafewpracticeproblemsonyourown.Workoneachoftheproblemsbelowand thenclickonthelinkattheendtocheckyouranswers. Problem1:Solve: log 5(4x + 11) =2 Problem2:Solve: log 2 (x + 5) - log 2(2x - 1) =5 Problem 3:Solve: log8 x + log8 (x + 6) = log8(5x +12) Problem 4:Solve: log 6 x + log 6(x - 9) =2 Problem5:Solve: ln(6x - 5) =3 Problem6:Solve: log 4 (3x - 2) - log 4(4x + 1) =2 Problem7:Solve: log 3(x 2 - 6x) =3 Problem8:Solve: log(x - 2) - log(2x - 3) =log 2 SolutionstoPracticeProblems